Peran Guru IPS Dalam Meningkatkan Sikap Sosial Dan Tanggung Jawab Siswa SMP Al-Washliyah 42 Berastagi - Winiya, Aina; Amini, Amini; Daulay, Alfiana; Amal, Wan Muhammad Ichlasul; Ocenia, Wilma Dearni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to (1) find out the role of social studies teachers in improving social attitudes and responsibilities at SMP Al-Washliyah 42 Berastagi; (2) Knowing the social attitudes of SMP Al-Washliyah 42 Berastagi; (3) Knowing the responsibilities of SMP Al-Washliyah 43 Berastagi; (4) Knowing the influence of the social studies teacher's role in improving the social attitudes of SMP Al-Washliyah 42 Berastagi students; and (5) to know the influence of social studies teacher's role in increasing the responsibility of SMP Al-Washliyah 42 Berastagi students. Where the teacher has a big role in determining and improving the social attitudes and responsibilities of students. The current role of the teacher is not only as an academic educator, but also as an educator for his students. Every teacher must be a motivator, corrector, and guide for students in forming their personal character. This makes the social studies teacher's role in improving the social attitudes and responsibilities of students at SMP Al-Washliyah 42 Berastagi in practice being an example for schools in cultivating social attitudes and student responsibility in order to achieve educational goals based on laws and regulations. This study aims to explain the role of social studies teachers in improving students' social attitudes and responsibilities inside and outside of learning at SMP Al-Washliyah 42 Berastagi. This research includes research with a qualitative approach to the type of research using descriptive methods. The method used by researchers is the method of interviews, observation, and documentation. The result of the research is that the social studies teacher's role in improving students' social attitudes and responsibilities in learning is as a motivator, corrector and mentor, initiator, facilitator, evaluator, demonstrator, organizer and informer. Meanwhile, the social studies teacher's role in improving students' social attitudes and responsibilities outside of learning is as a guide, evaluator, demonstrator, and as a proofreader. The social studies teacher's obstacles in forming social attitudes and responsibilities are 1. The teacher cannot always monitor the behavior of students because the teacher's task is not only to teach but also to carry out other tasks, 2. The evaluation is not as maximal as possible, 3 The environmental situation does not support implementing formation of social attitudes and maximum responsibility. Keywords: teacher's role, social attitude, responsibility, social studies teacher